Economics without borders : economic research for European policy challenges - Blundell, Richard (Cambridge : Cambridge University Press, 2012)
If treated as a single economy, the European Union is the largest in the world, with an estimated GDP of over 14 trillion euros. Despite its size, European economic policy has often lagged behind the rest of the world in its ability to generate growth and innovation. Much of the European economic research itself often trails behind that of the USA, which sets much of the agenda in mainstream economics. This book, also available as open access, bridges the gap between economic research and policymaking by presenting overviews of twelve key areas for future economic policy and research. Written for the economists and policymakers working within European institutions, it uses comprehensive surveys by Europe's leading scholars in economics and European policy to demonstrate how economic research can contribute to good policy decisions, and vice versa, demonstrating how economics research can be motivated and made relevant by hot policy questions.
Title from publisher's bibliographic system (viewed on 19 Jun 2019).
Open Access title.
Keywords: Economics -- Research -- European Union countries; European Union countries -- Economic policy